Aquifer Geometry and Water Quality in Relation to Occurrence and Distribution of Peat in Baghia-Chanda Beel, Bangladesh (Journal of Scientific Research, 2016)
Baghia-Chanda Beel, largest peat basin in Madaripur and Gopalganj (Bangladesh) districts occupies thick deposits of peat. Study focuses on the aquifer geometry and geochemical evaluation of groundwater in relation to occurrence and distribution of peat. Landuse map is generated to show the surface distribution of peat. Thick peat and clay layer respectively, with an average thickness of 7 ft, has been observed throughout the study area. Principal productive aquifer about 40 ft thick, is found at depth between 35 to 145 ft below ground surface. According to pH and EC values, groundwater is mildly acidic to slightly alkaline and fresh to brackish. High bicarbonate concentration which is more likely to be attributed from the oxidative degradation of peat is found at shallow aquifer below peat. Elevated sodium (Na+) and chloride (Cl-) concentrations in deep aquifer are due to the trapping of ancient sea water in the subsurface during Quaternary period. Although  deep aquifer is extensively low in arsenic, 68% and 44% shallow groundwater samples are arsenic (As) contaminated according to WHO, 2011 and Bangladesh Drinking Water Standard (DoE, 1997) limit respectively. Assessment of Water Quality Indexes (WQI>100) suggests that water from deep aquifer is more suitable for drinking purposes.